ANALISIS PERAN HUMAN CAPITAL DAN MOTIVASI BERPRESTASI TERHADAP KEMAMPUAN GURU DALAM MELAKUKAN TRANSFER OF KNOWLEGDE PADA MASA PANDEMI COVID-19 - Edi Jusriadi; Masnaeni Mansyur Tiara (COMPETITIVENESS, 2021)
This study aims to explain the role of human capital and achievement motivation in the ability of teachers to transfer of knowledge in the midst of the Covid-19 pandemic. This type of research is a qualitative descriptive study. The informant in this study was a teacher at Madrasah Ibtidaiyah YPRI Wawondula. Data collection techniques were carried out by observation, interviews and documentation. The data analysis technique used by researchers is data reduction and triangulation. The results of the study are: The role of Human Capital or teachers is very influential on the ability of achievement motivation, Teachers are required to become learner teacher and master in information technology related to the use of online learning applications, teachers must be able to provide material that attracts students' attention So that teachers must take various kinds of training to master online learning applications to attract more students to learn online in the during COVID-19 pandemic. After participating in training on the use of online learning applications and providing additional incentives for purchasing internet quotas, the teachers are increasingly motivated to be more creative in making learning materials that attract students to learn. Keywords: Human Capital, Achievement Motivation and Teacher Ability.